The Fundamentals of Global Governance - Whitman, J. author. aut Link
XIII, 187 p.
Keywords: What kind of activity is global governance? What do all of the many sectoral forms of global governance – of the planetary environment, of global finance and global health – have in common? Moving beyond sector-specific studies, this book outlines the fundamentals of global governance in eight chapter-length propositions.